Abnormal ventricular activation and repolarisation during dobutamine stress echocardiography in coronary artery disease. Issue 5 (1st May 1998) - O'Sullivan, C A; Henein, M Y; Sutton, R; Coats, A J S; Sutton, G C; Gibson, D G
Abstract : Objective: To assess possible ECG changes caused by dobutamine stress and their relation to wall motion disturbances in patients with coronary artery disease. Design: Prospective recording and analysis of 12 lead ECG at rest and during each stage of dobutamine stress echocardiography, and correlation with wall motion changes. Setting: A tertiary referral centre for cardiac disease equipped with non-invasive facilities for pharmacological stress tests. Subjects: 27 patients, mean (SD) age 60 (8) years, with documented evidence of coronary artery disease in whom dobutamine stress echo was clinically indicated, and 17 controls of similar age. Results: In controls, all ECG intervals shortened with increasing heart rate but in the patient group only PR and QT intervals shortened while QRS duration broadened and QTc interval prolonged progressively. In the 27 patients, 16 developed chest pain, 15 with reduced left ventricular long axis systolic excursion (p < 0.001), and all showed reduced peak lengthening rate; ST segment shift appeared in 16, 13 of whom developed chest pain, but did not correlate with reduction of either systolic long axis excursion or peak lengthening rate; QRS duration broadened in 20, 16 with reduction of long axis excursion (p < 0.02) which was more often seen at the septum (p < 0.005); QTc interval prolonged in 19, all of whom had associated reduction of peak long axis lengthening rate (p < 0.02). Conclusions: QRS duration and QTc interval both normally shorten with dobutamine stress, while in coronary artery disease they both lengthen: changes in QRS duration correlate with systolic and QTc interval with diastolic left ventricular wall motion disturbances. ST segment shift also occurred in most patients, but without consistent correlation with wall motion abnormalities. It was thus less discriminating than the other two abnormalities in this respect.